Variability and energy budget of the baroclinic tides in the Arabian Sea - Ma, Jingyi; Guo, Daquan; Zhan, Peng; Hoteit, Ibrahim (Frontiers in Marine Science, 2023)
A 3D high-resolution general ocean circulation model was implemented and validated to study the characteristics and seasonal variability of the internal tides in the Arabian Sea (AS). Three major source locations of internal tides were identified: Socotra Island, the northeastern shelf area of AS, and the Maldives. Around Socotra Island, internal tides propagate both southward and northward, before quickly dissipating. The internal tides generated in the northeastern AS split into two branches: Branch-I propagates perpendicular to the shelf, whereas Branch-II propagates more southernly. The internal tides originated in the Maldives propagate almost latitudinally both eastwards and westwards. Generally, the internal tides in the AS are more pronounced in January as shown by the forcing function, energy flux, and conversion rate. The hourly average conversion rate for the entire domain, including the AS, the Red Sea, and the Arabian Gulf -was 34.28 GW in January and 20.51 GW in July, suggesting a slightly larger barotropic-to-baroclinic conversion rate in January, probably due to the strong stratification around 100 meters in winter.